1999
DOI: 10.2466/pms.1999.88.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Test-Retest Reliability of the Hurlbert Index of Sexual Assertiveness

Abstract: This study investigated the test-retest stability of the Hurlbert Index of Sexual Assertiveness. 54 nonclinical and 46 clinical subjects were administered the Index on two occasions 4 wk. apart. Test-retest correlation coefficients were calculated separately and together. The results evidenced high test-retest reliability. Correlation coefficients were .88 for nonclinical subjects and .83 for clinical subjects with an over-all test-retest reliability of .85 for all 100 subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 5 publications
3
10
0
1
Order By: Relevance
“…The summation of each item provides a global score of sexual assertiveness ranging from 0 to 100, higher scores representing a better capacity to be assertive with sexual partners. Reliability and validity have been well demonstrated (Apt & Hurlbert, 1992;Hurlbert, 1991;Pierce & Hurlbert, 1999). In the current sample, Cronbach's alphas were .91 and .89 respectively for women and men.…”
Section: Sexual Assertivenessmentioning
confidence: 91%
See 1 more Smart Citation
“…The summation of each item provides a global score of sexual assertiveness ranging from 0 to 100, higher scores representing a better capacity to be assertive with sexual partners. Reliability and validity have been well demonstrated (Apt & Hurlbert, 1992;Hurlbert, 1991;Pierce & Hurlbert, 1999). In the current sample, Cronbach's alphas were .91 and .89 respectively for women and men.…”
Section: Sexual Assertivenessmentioning
confidence: 91%
“…The concept of sexual assertiveness refers to the ability to communicate openly about sexual matters including the initiation of sexual activity, refusal of unwanted sexual activities, communication of sexual preferences and negotiation of desirable sexual behavior such as contraceptive use and safer-sex behavior (Morokoff et al, 1997;Pierce & Hurlbert, 1999). The ability to assert one's sexual preferences seems to be impaired in women with attachment anxiety, who may be more likely to respond to their partners' sexual needs rather than to their own (Davis et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Results of mean scores reveal that assertiveness still follows traditional sexual scripts and gender-role stereotypes, especially among older participants. According to this, men assertively initiate sexual contacts more frequently than women (Haavio-Mannila & Kontula, 1997;López, Carcedo, Fernández-Rouco, Blázquez, & Kilani, 2011;Pierce & Hurlbert, 1999;Snell, et al, 1991) because they are supposed to initiate sexual contacts while women are supposed to act as restrictors of such contacts (Simon & Gagnon, 1984, 1986, 2003. In addition, young women scored slightly higher than young men on the No Shyness/Refusal subscale, which indicates that young women are less shy and refuse sexual contacts more often than young men.…”
Section: Discussionmentioning
confidence: 98%
“…In general, results have usually found that men scored higher than women on sexual assertiveness (Haavio-Mannila & Kontula, 1997;Pierce & Hurlbert, 1999;Snell, Fisher, & Miller, 1991), although results have been mixed (Stulhofer, Graham, Bozicevic, Kufrin, & Ajdukovic, 2007). For example, Pierce and Hurlbert (1999) interviewed 54 non-clinical individuals and 46 clinical individuals attending sex therapy and showed that men in both clinical and non-clinical samples scored higher on sexual assertiveness than women. On the other hand, Sutlhofer et al (2007) interviewed a nationally representative sample of young men and women and found that women scored higher than men on sexual assertiveness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation